Implementing a Chronic Disease Self-Management Program into China: The Happy Life Club™ - Browning, Colette Joy; Yang, Hui; Zhang, Tuohong; Chapman, Anna; Liu, Shuo; Enticott, Joanne; Thomas, Shane Andrew (Frontiers in Public Health, 2015)
.